Mid-Term Anatomic Results after Endovascular Treatment of Ruptured Intracranial Aneurysms with Guglielmi Detachable Coils and Matrix Coils: Analysis of the CLARITY Series - Pierot, L. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: Matrix coils have been developed to prevent aneurysm recanalization. Midterm anatomic results in a prospective multicenter consecutive series including patients treated with GDC or Matrix coils for ruptured aneurysms are presented. MATERIALS AND METHODS: Five hundred seventeen patients harboring ruptured aneurysms were treated with GDC (276 patients) or Matrix coils (241 patients). Postoperative and midterm anatomic results were evaluated anonymously and independently using the Modified Montreal Scale (complete occlusion, neck remnant, and aneurysm remnant). RESULTS: In the midterm follow-up (mean, 16.7 months in the GDC group and 15.4 months in the Matrix group), complete occlusion was reported in 95/276 aneurysms (34.4%) in the GDC group and 80/241 (33.2%) in the Matrix group, neck remnant in 127/276 (46.0%) in the GDC group and 118/241 (49.0%) in the Matrix group, and aneurysm remnant in 54/276 (19.6%) in the GDC group and 43/241 (17.8%) in the Matrix group. Evolution of aneurysm occlusion was improvement in 35/272 aneurysms (12.9%) in the GDC group and 27/239 (11.3%) in the Matrix group, stable situation in 98/272 (36.0%) in the GDC group and 97/239 (40.6%) in the Matrix group, and worsening in 139/272 (51.1%) in the GDC group and 115/239 (48.1%) in the Matrix group. A total of 32/517 patients were retreated during the follow-up period: 9/276 (3.3%) in the GDC group and 23/241 (9.5%) in the Matrix group (P = .003). CONCLUSIONS: In this study, midterm anatomic results and evolution of aneurysm occlusion were not different in patients with ruptured aneurysms treated with GDC or Matrix coils.